(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Liposomes are one of the highly placed acquisitions of the pharmaceutical industry and also help multiple delivery system target a drug to a significant tissue. Owing to the similarity in structure of both the cell membrane and the lipid bilayer, liposomes are easily unfused in the drug delivery to prevent penetration of a free drug. Liposomes further have the ability to encapsulate in hydrophobic and hydrophilic materials, which is then used in drug delivery carriers. Such a technology is highly useful to treat certain diseases. As of now, huge traction is driven towards using Liposomes. The crucial object of the said technology’s review is the fact that they are effective in treating certain diseases, can be easily prepared and has more benefits as compared to others. Liposomes as seen are biocompatible, with several applications starting from delivering antiviral, antibacterial drugs, enzymes, fungicides, antiparasite drugs, diagnostic tools, transdermal transporters, and adjuvant for varied vaccines. The given paper is seen to focus mainly on scalable techniques and strength, with limitations in regards to its application in industry, and the regulatory requirements relating to the drug formations liposomal on the basis of EMEA and FDA documents.